Strategi Pendekatan Orientasi Kewirausahaan, Orientasi Pasar dan Pembelajaran Organisasi dalam Meningkatkan Kinerja UMKM Makanan Halal Khas Cirebon - Yuliana, Rahmi; Widowati, Maduretno (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
The purpose of this study was to examine the effect of entrepreneurial orientation, market orientation and organizational learning on the quality of strategic assets, and also the effect of the quality of strategic assets on the performance of the Cirebon halal food SMEs. This research was conducted on the Cirebon Typical Halal Food UMKM, the respondents used were 200 respondents. The data was processed using Structural Equation Modeling (SEM) with the help of the Analysis of Moment Structure (AMOS) program version 23.0. Based on the results of the analysis, it can be concluded that the effect of entrepreneurial orientation on strategic asset quality shows a CR value of -0.338 and with a probability of 0.735, testing the effect of entrepreneurial orientation on business performance shows a CR value of 2.499 and with a probability of 0.012, market orientation towards strategic asset quality shows a CR value. of 2.344 and with a probability of 0.035, market orientation to business performance shows a CR value of 2.362 and with a probability of 0.031, testing organizational learning on strategic asset quality shows a CR value of 4.881 and with a probability of 0.001., testing the effect of organizational learning on business performance shows a CR value of 1.351 and with a probability of 0.177, the effect of strategic asset quality on business performance shows a CR value of 2.067 and a probability of 0.039. Kata Kunci : Orientasi Kewirausahaan, Orientasi Pasar, Pembelajaran Organisasional, Kualitas Aset stratejik, Kinerja Bisnis